Experimental investigation on the effect of crystal birefringence on the performance of nanosecond-pulsed diamond Raman laser - Yongpeng Yan; Xuezong Yang; Muye Li; Yuxiang Sun; Huawei Jiang; Shulong Zhang; Chengchun Zhao; Yin Hang; Yan Feng (Functional Diamond, 2025)
The impact of crystal birefringence on the performance of diamond Raman lasers has been studied previously at power levels slightly above the threshold. However, the diamond Raman lasers operating far above the threshold usually exhibit different properties. Using the Metripol polarimetry, we obtained the birefringence intensity and fast-axis distribution of a home-made single-crystal diamond. The effects of crystal birefringence on the performance of Stokes laser were then investigated in an external nanosecond-laser pumped Raman cavity with a low Q-factor. When the pump power exceeds 1.5 times the Stokes threshold, the Stokes output performance is significantly affected by birefringence, if the birefringence intensity is high or the fast axis angle is far from the diamond maximum gain angle. In regions where the birefringence intensity is low and the fast axis angle is close to the maximum gain direction, the output is mainly influenced by gain variations. This work can provide valuable insights for the development of single-crystal diamond and polarization-related nanosecond-pulsed diamond Raman laser applications.